Management in the age of digital business complexity - McKelvey, Bill (Routledge studies in innovation, organizations and technology, 2021)
"Management in the Age of Digital Business Complexity focuses on how the digital age is changing management and vastly speeding up complexity dynamics. The recent coevolution of technologies has dramatically changed in just a few years how people and firms learn, communicate, and behave. Consequently, the process of how firms coevolve and the speed at which they coevolve has been dramatically changed in the digital age, and managerial methods are lagging way behind. Combining his own expertise with that of a number of specialist and international co-authors, McKelvey conveys how companies that fall behind digitally can quickly be driven out of business. The book has been created for academics seeking to upgrade management thinking into the modern digital age and vastly improve the change capabilities of firms facing digital-oriented competition"--